The Impact of L2 English Learners' Belief about an Interlocutor's English Proficiency on L2 Phonetic Accommodation - Jiang, Fan; Kennison, Shelia (Journal of psycholinguistic research, 2022)
The current study investigates the influence of L2 English learners’ belief about their interlocutor’s English proficiency on phonetic accommodation and explores whether interaction-induced phonetic convergence could improve L2 English learners’ vowel pronunciation. Results from two experiments show that when the subjects believed that their interlocutor was a native English speaker, they generally converged to her vowel pronunciation. When the subjects believed that their interlocutor was a non-native English speaker, they generally diverged from her vowel pronunciation. In addition, phonetic convergence enabled the subjects to improve their L2 English vowel pronunciation, leading to greater similarity to the native interlocutor. The findings are discussed in terms of the Communication Accommodation Theory, the Interactive Alignment Theory, and the Speech Learning Model.